Adsorption of Cu(ii) ions in aqueous solution by aminated lignin from enzymatic hydrolysis residues. Issue 71 (19th September 2017) - Xu, Jun; Zhu, Shiyun; Liu, Peng; Gao, Wenhua; Li, Jun; Mo, Lihuan
Abstract : Aminated lignin (AL) has been prepared by a Mannich reaction for the removal of Cu(ii ) ions from aqueous solution. Abstract : Aminated lignin (AL) has been prepared by a Mannich reaction for the removal of Cu(ii ) ions from aqueous solution. Effects of pH, reaction temperature, reaction time and the initial concentration of Cu(ii ) ions on the adsorption capacity were investigated. The structure and properties of AL were analyzed by Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy analysis (SEM), and X-ray photoelectron spectroscopy analysis (XPS). Adsorption kinetic and isotherm models were used to illustrate the adsorption behaviors of AL. AL was more effective than enzymatic hydrolysis residues (EHR) and separated lignin (SL) in removing Cu(ii ) ions in aqueous solution. The adsorption capacity of AL for Cu(ii ) ions was better in near-neutral pH. Under the optimum adsorption conditions, the adsorption capacity of AL could reach up to 37.14 mg g −1 . The pseudo-second-order model fitted the kinetic data well. The adsorption isotherm was well described by the Langmuir isotherm model. AL exhibited a good adsorption performance for recovery after three cycles. AL could be utilized as a kind of promising feedstock for high value-added products to remove Cu(ii ) ions in wastewater effectively.